Microbiota, Epithelium, Inflammation, and TGF-β Signaling: An Intricate Interaction in Oncogenesis - Pang, Xin; Tang, Ya-jie; Ren, Xiao-hua; Chen, Qian-ming; Tang, Ya-ling; Liang, Xin-hua (Frontiers in Microbiology, 2018)
Microbiota has been widely considered to play a critical role in human carcinogenesis. Recent evidence demonstrated that microbiota, epithelial barrier and inflammation has made up a tightly interdependent triangle during the process of carcinogenesis. Hence, we discussed the triangle relationship of microbiota dysbiosis, epithelial barrier dysfunction and dysregulated immune responses to elucidate the mechanisms by which microbiota induces carcinogenesis, especially highlighting the reciprocal crosstalk between transforming growth factor-β signaling and every side of the tumorigenic triangle. This sophisticated interaction will provide insight into the basic mechanisms of carcinogenesis and may bring new hope to cancer prevention and therapeutic intervention.